2008
DOI: 10.1002/jbm.a.32075
|View full text |Cite
|
Sign up to set email alerts
|

In vivo human electrochemical properties of a NiTi‐based alloy (Nitinol) used for minimally invasive implants

Abstract: The development of a homemade device for in vivo human determination of the open circuit potential (OCP) of Nitinol is described. Pseudo-reference electrodes (316L stainless steel and Pt) were initially tested and validated in vitro using simulated body fluids. As judged from the excellent electrochemical responses in terms of both accuracy and precision, the most ideal system comprised the combination of sterilized Pt (pseudo-reference) and Nitinol (working) needle-shaped electrodes. The average in vivo human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Its properties forming a boundary layer contacting an aqueous electrolyte were well characterized by the circuit diagrams obtained from EIS. The measured open circuit potentials of NiTi using 1%NaCl and PBS corresponded well to potentials retrieved in vivo [20], but the potentials obtained utilizing serum differed. It can be carefully concluded that serum provides a physiological environment but findings in vitro can not necessarily be transferred to conditions in vivo as the body environment is electrochemically aggressive to biomaterials.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Its properties forming a boundary layer contacting an aqueous electrolyte were well characterized by the circuit diagrams obtained from EIS. The measured open circuit potentials of NiTi using 1%NaCl and PBS corresponded well to potentials retrieved in vivo [20], but the potentials obtained utilizing serum differed. It can be carefully concluded that serum provides a physiological environment but findings in vitro can not necessarily be transferred to conditions in vivo as the body environment is electrochemically aggressive to biomaterials.…”
Section: Discussionmentioning
confidence: 60%
“…Applications of in vitro corrosion analyses include the characterization of surface modifications [9,11,13,14], coatings [5,8,10,12,15,16] and new materials [6,17,18]. In vivo OCP measurements have been performed in dogs [19] and humans [20]. The majority of the studies found that the surface features crucially influence corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It was mentioned that this kind of experiments was substantially investigated 30 years ago (Steinemann, 1980). For a short duration of experiments, these investigations, in human body, were performed with Nitinol alloy involved in manufacturing stents dedicated for blocked arteries (Pertile, 2008). The short experiments do not allow predicting the corrosive behavior for a long time.…”
Section: Biocorrosion Of Implants -Discussion and Future Directionsmentioning
confidence: 99%
“…Pertile et al recently measured the open-circuit potential (OCP) of NiTi in vivo in humans [102]. They determined the average in vivo human OCP determined from six independent measurements on human patients in the arterial system was À 0.334 AE 0.030 V (SCE).…”
Section: B9 Corrosion Of Niti Medical Devicesmentioning
confidence: 99%
“…This value was in good agreement with their data from in vitro testing using simulated body fluids [ À 0.313 AE 0.003 V (SCE) in AFNOR S90-701 artificial saliva, À 0.334 AE 0.001 V/SCE in artificial urine, and À 0.239 AE 0.007 V/SCE in Ringer's solution]. They noted that, since no E b values were reported lower than 0.0 V/SCE, NiTi should be considered resistant to pitting in vivo [102].…”
Section: B9 Corrosion Of Niti Medical Devicesmentioning
confidence: 99%